Tree Volume Tables for Eucalyptus grandis - Pande, G. C.; Jain, R. C. (Indian Forester, 1976)
Large scale plantations of Eucalyplus grandis have been raised in the high lands of Kerala and in the Nilgiris in Tamilnadu. The wood from these plantations will be mainly used for the production of pulp. Previous tables (A.N. Chaturvedi, Ind. For. Ree., Vol 12, No. 17) were based on the regression of volume on the variable D-H (D=diatmeter, and H=height of a tree). These tables were based on a measurement of 149 trees. The determination coefficient was quite high for this regression (0.99). Regression of, âˆšV was further fitted on variable D (R2=O.97). A new analysis has been attempted, as (i) the number of trees measured now is 233 and the data naturally covers more trees of higher age classes and (ii) it was not considered worthwhile to restrict the fitting of regression to one variable only.